Inhalation toxicity of copper compounds: Results of 14-day range finding study for copper sulphate pentahydrate and dicopper oxide and 28-day subacute inhalation exposure of dicopper oxide in rats. (30th May 2022) - Poland, Craig A.; Hubbard, Sue A.; Levy, Len; Mackie, Carol
Abstract: Inhalation exposure to copper may occur during a range of occupational activities and the purpose of this study was to characterise the toxicological response to repeated inhalation of two copper compounds, representative of copper substances in large-scale production/use. Crl:CD(SD) rats were repeatedly exposed to aerosols of dicopper oxide (Cu2 O) or copper sulphate pentahydrate (CuSO4 .5 H2 O) for 14-days as part of a range finding study at normalised copper doses of 0.18, 0.71, 1.78 and 8.9 mg/m 3 Cu. Within a 28-days main study (Cu2 O only), animals were repeatedly exposed to 0.2, 0.4, 0.8 and 2.0 mg/m 3 Cu2 O following OECD TG 412. The main study also consisted of satellite groups exposed for 1-, 2- or 3- weeks as well as a 13-week post-exposure recovery period group. Repeated exposure for 14-days to both copper compounds, normalised for copper content, led to an acute influx of polymorphonuclear leukocytes (neutrophils) and macrophages whilst only CuSO4 .5 H2 O exposure resulted in epithelial hyperplasia. This differential response may reflect the highly dissolvable nature of CuSO4 .5 H2 O in lung lining fluid leading to a release of copper ions at the epithelial surface whilst Cu2 O is relatively indissolvable at neutral pH. In the 28-day study with Cu2 O, an increase in cellularity was also evident in both histological and BALF samples and was dose-related with minimal to mild (neutrophilic) inflammation observed > 0.4 mg/m 3 in the lung tissue sections and significant increases from 0.2 mg/m 3 in BALF. There were no minimal haematological findings, no clinical findings and systemic organs were unaffected by inhalation exposure to dicopper oxide. The lung cellular response was limited to alveolar histiocytosis and neutrophil influx with no evidence of epithelial hyperplasia or fibrosis and all lung biomarkers returned to control levels within the post-exposure recovery period. Interestingly, the satellite groups showed that this acute cellular response followed a biphasic rather than monotonic pattern with a peak in lung biomarkers between weeks 1–3 and reduction thereafter. This reduction in lung biomarkers occurred during continued exposure and may indicate an adaptive response to copper exposure. Overall, these results show that repeated exposure to copper compounds results in an acute cellular response with no associated pathology and which fully resolved after the cessation of exposure. Therefore, the cellular response is evidence of a controlled and adaptive response associated with the removal of Cu2 O from the alveolar surface. Highlights: Rodents were repeatedly exposed via inhalation to two Cu compounds. Sub-acute exposure to Cu compounds resulted in a dose-related cellular response. The response peaked between weeks 1–3 then reduced despite ongoing exposure. The response resolved by the end of a 13-week recovery period. The effect was confined to a cellular response with no associated pathology.